Global, regional, and national burden of gastric cancer attributable to diet high in sodium from 1990 to 2021 - Ma, Chao; Yan, Bing; Li, Ge; Jiang, Yongsheng (Frontiers in Nutrition, 2025)
BackgroundThis study, based on the Global Burden of Disease (GBD) 2021 database, investigates the global and regional burden of gastric cancer attributable to diet high in sodium (GC-DHIS) from 1990 to 2021 and projects trends through 2045, with the aim of providing evidence to inform public health policymaking.MethodsData were obtained from GBD 2021, covering 204 countries and territories. Disability-adjusted life years (DALYs) were used as the primary metric. The Das Gupta method was applied to decompose the drivers of changes in disease burden, and the Nordpred model was used to forecast future trends.ResultsBetween 1990 and 2021, the global number of DALYs attributable to GC-DHIS decreased by 2%, while deaths increased by 12%. The largest absolute number of DALYs was observed in middle SDI regions, whereas the most rapid growth occurred in low-middle SDI regions. Health inequality analysis revealed that the burden of GC-DHIS was disproportionately concentrated in regions with higher levels of social development. Projections from 2022 to 2045 suggest a significant increase in DALYs and deaths, with a faster rise among males. However, age-standardized DALY rates (ASDR) and age-standardized mortality rates (ASMR) are expected to decline substantially.ConclusionDespite the global decline in ASDR and ASMR of GC-DHIS, the absolute burden is expected to rise in specific regions and populations, highlighting the need for targeted prevention and control strategies.